The requirement of uncoordinated 51-like kinase 1 (ULK1) and ULK2 in the regulation of autophagy - Lee, Eun-Ju (Landes Bioscience, 2011)
Autophagy is an evolutionarily conserved physiological process of self-digestion by a cell to adapt to various stresses, including starvation. Its molecular basis involves the concerted activation of proteins encoded by the family of autophagy-related (Atg) genes. The best characterized is the serine/threonine protein kinase Atg1 in yeast which appears to be essential at the early stage of autophagy. In mammals, five Atg1 homologues have been identified as uncoordinated (UNC) 51-like kinase 1 to 4 and STK36. ULK1 and ULK2 are the most closely related members of the family, sharing 78% homology within their protein kinase domains. However, the specific function of ULK1 and ULK2 in mammalian autophagy is not fully understood. Here, we demonstrate that ULK1 and ULK2 are functionally redundant protein kinases required to mediate autophagy under nutrient-deprived conditions in fibroblasts. In contrast, ULK1, but not ULK2, is critical to induce the autophagic response of cerebellar granule neurons (CGN) to low potassium concentration in serum-free conditions. Furthermore, we found that ULK1 has a cytoprotective function in neurons. Together, these results provide strong genetic evidence that ULK1 is an essential component of the autophagic signaling pathway. The ability of ULK2 to compensate for the loss of ULK1 function is cell-type specific.